The Balance of Ahl al-Sunnah wa al-Jama’ah in the Concept of Belief in Allah Almighty - Dr. Ibrahim bin Mian Jan; Dr. Zia Ur Rahman bin Jameel Ur Rahman (Journal of Religion and Society, 2025)
This study addresses one of the most significant issues in Islamic creed, namely the concept of faith (īmān) in Allah Almighty, with a focus on clarifying the balance of Ahl al-Sunnah wa al-Jamā‘ah in this matter and affirming it as the sound methodology followed by the righteous predecessors of the Ummah, including the Companions, the Successors, and those who followed them with excellence. The study begins by highlighting the importance of moderation in matters of faith and explaining that deviation from this balanced approach was a major cause of the emergence of sects, disagreement, and fragmentation within the Muslim community, particularly in issues of creed. The research is divided into three main sections. The first section examines the concept of balance according to Ahl al-Sunnah wa al-Jamā‘ah through a linguistic and legal analysis of the term wasat (balance), clarifying its various meanings such as justice, goodness, virtue, balance, and moderation between the extremes of excess and negligence. It demonstrates that these meanings form the foundation upon which the creed of Ahl al-Sunnah wa al-Jamā‘ah is established in all aspects of religion, most notably in the chapter of faith. The second section is devoted to explaining the concept of faith in Allah Almighty according to Ahl al-Sunnah wa al-Jamā‘ah. It establishes that faith consists of confession by the tongue, belief in the heart, and actions of the limbs; that it increases with obedience and decreases with disobedience; that believers vary in their levels of faith; and that faith has a foundation and branches, such that it is not nullified by the loss of some of its branches as long as its foundation remains intact. This position is supported by abundant evidence from the Qur’an, the Sunnah, the quotations of the Companions, and the consensus of the early scholars, along with a distinction between absolute faith (al-īmān al-muṭlaq) and the mere presence of faith (muṭlaq al-īmān), and an explanation of the three levels of faith: recommended perfection, obligatory perfection, and the basic level of faith.The third section presents the views of those who opposed Ahl al-Sunnah wa al-Jamā‘ah regarding the concept of faith, namely the Khārijites and the Mu‘tazilites on one side, and the Murji’ah in their various groups on the other. The study clarifies how each group deviated from the path of balance: the extremists regarded faith as a single, indivisible entity and declared sinners to be outside the fold of faith or guilty of disbelief, while the Murji’ah excluded deeds from the definition of faith and granted false security to sinners from divine punishment. The study concludes that the methodology of Ahl al-Sunnah wa al-Jamā‘ah represents the just, balanced position that reconciles the scriptural texts, realizes justice and mercy, and preserves the religion for people without excess or negligence. Keywords: Faith, Balance, Ahl al-Sunnah wa al-Jamā‘ah, Islamic Creed, Increase and Decrease of Faith, Deviant Sects